Evaluation of Signal-in-Space Continuity and Availability for BeiDou Satellite Considering Failures. (14th March 2020) - Fan, Lihong; Tu, Rui; Zheng, Zengji; Zhang, Rui; Lu, Xiaochun; Liu, Jinhai; Huang, Xiaodong; Hong, Ju
Abstract : Signal-in-space (SIS) continuity and availability are important indicators of performance assessment for Global Navigation Satellite Systems (GNSSs). The BeiDou Navigation Satellite System (BDS) Open Service Performance Standard (BDS-OS-PS-1.0) has been released, and the corresponding public performance indicators have been provided, but the actual SIS performance is uncertain to users. SIS continuity and availability are primarily related to unscheduled outages (failures). Therefore, based on the existing failure classification system and actual operation modes, four types of failure modes are first analysed: long-term failure related to satellite service period, maintenance failure related to satellite manoeuvring, short-term failure associated with random repairable anomalies and equivalent failure corresponding to a combination of the above three types of failures. Second, based on the failure classification and selected precise and broadcast ephemerides from 2015–2016, the Mean Time Between Failure (MTBF) and Mean Time To Repair (MTTR) of each failure type are obtained using appropriate detection methods. Finally, using a corresponding assessment model, the SIS continuity and availability of BeiDou are calculated for individual and equivalent failure cases, and these are compared with the provided index in the BDS Open Service Performance Standard.